OP0155-HPR EFFECT OF THE DR. BART APPLICATION ON HEALTHCARE USE AND CLINICAL OUTCOMES IN PEOPLE WITH OSTEOARTHRITIS OF THE KNEE AND / OR HIP IN THE NETHERLANDS; A RANDOMIZED CONTROLLED TRIAL. (2nd June 2020) - Pelle, T.; Bevers, K.; Van der Palen, J.; Van den Hoogen, F.; Van den Ende, C.
Abstract : Background: Self-management is of paramount importance in non-surgical treatment of knee and/or hip osteoarthritis(OA). Modern technologies offer the possibility to support self-management 24/7. We developed an e-self-management application (dr. Bart app) for people with knee and/or hip OA. A central element of the dr. Bart app is that the app proposes a selection of 72 preformulated goals to induce health behaviors based on the 'tiny habits method' 1 Objectives: To evaluate the short-term effects of the use of the dr. Bart app, compared to usual care, on the number of secondary health care consultations and clinical outcomes in people with knee/hip OA in the Netherlands. Methods: A randomized controlled design involving participants ≥50 years with self-reported knee and/or hip OA, randomly allocated to the dr. Bart app or usual care. Participants were recruited from the community through advertisements in local newspapers and social media campaigns. In Figure 1 the theoretical framework of the dr. Bart app is presented. Participants received online questionnaires at baseline and after 3 and 6 months of follow-up. The primary outcome was the number of consultations in secondary health care due to OA in the knee/hip in the past six months. Secondary outcome measures were self-management behavior, pain, symptoms, functional limitations, physical activity, quality of life, and illness perceptions. Data were analyzed using negative binomial regression or linear mixed models, as appropriate, corrected for baseline, main OA-location (knee or hip), and interaction between treatment group and time. Results: In total 427 eligible participants were allocated to either the dr. Bart group (n=214) or usual care (n=213). Mean age of the participants was 62.1 (SD 7.3) years, with the majority being female (72%) and having symptoms predominantly in their knee(s) (73%). Response rates for the follow-up questionnaires were 75.4% and 69.3% at 3 and 6 months, respectively. With respect to the number of consultations in secondary health care we found a non-significant incidence rate ratio (1.20 (95% CI: 0.67; 2.19)) between the dr. Bart app group and the usual care group. We found a positive overall treatment effect of the dr. Bart app on symptoms (2.6 (95% CI: 0.4; 4.9)), pain (3.5 (95% CI: 0.9; 6.0)) and, activities of daily living (2.9 (95% CI: 0.2; 5.6)), see Table 1 . We found non-significant differences between groups for self-management behavior, physical activity, health-related quality of life and illness perceptions. Conclusion: The dr. Bart app did not reduce the number of secondary health care consultations compared to usual care. However, we found positive effects attributable to the dr. Bart app on pain, symptoms, activities of daily living and functioning in sport and recreation in people with knee/hip OA, suggesting that the dr. Bart app has potential to positively influence health in people with knee/hip OA. References: [1]Fogg GJ. 2009: ACM; 2009: 40. Disclosure of Interests: None declared